2018
DOI: 10.5121/ijcsit.2018.10303
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining Model Performance of Sales Predictive Algorithms Based on Rapidminer Workflows

Abstract: By applying RapidMiner workflows has been processed a dataset originated from different data files

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
0
19
0
1
Order By: Relevance
“…• Requirements related to the management of the site and its maintenance. All the user feedbacks and sales results are used for the optimization of the web page by means of a data mining algorithms able to enhance clusters of products most sold and to predict demand marketing (time series forecasting prediction [23]- [24]).…”
Section: Web Marketingmentioning
confidence: 99%
“…• Requirements related to the management of the site and its maintenance. All the user feedbacks and sales results are used for the optimization of the web page by means of a data mining algorithms able to enhance clusters of products most sold and to predict demand marketing (time series forecasting prediction [23]- [24]).…”
Section: Web Marketingmentioning
confidence: 99%
“…In this direction, ANN could predict patient physiological status [17], could be applied for predictive medicine [18], and for the prediction of heart problems [19], suggesting ANN as a good approach to predict patient health status in DSS. In particular, ANN applied in other applications exhibited high performances [20], specifically MLP-ANN provided a good match between experimental and predicted results [21], and good flexibility concerning predictive maintenance and big data analytics [22].…”
Section: Background: Tools and Specifications Useful For Rmp-dss Designmentioning
confidence: 99%
“…A similar conclusion was also drawn in [42], noting the ease of KNIME to gain insight into data. While [43] favored Rapid…”
Section: Data Mining For Sme: a Modelmentioning
confidence: 99%
“…Miner given that workflows can be created to represent several methodologies. It has been observed that the development of an Artificial Neural Network (ANN) was the best predictor for future sales, essentially using historical data and examples to form a conscious within the system which can then be used to predict future events [43]. In another research, it was noted that an ANN to have three layers, Figure 6, with the hidden layer being the analysis of the data to find relationships between the variables [44].…”
Section: Data Mining For Sme: a Modelmentioning
confidence: 99%